2008
DOI: 10.30843/nzpp.2008.61.6885
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide selection for wandering Jew (<i>Tradescantia fluminensis</i>) control

Abstract: Wandering Jew (Tradescantia fluminensis) prevents the regeneration of native forests in New Zealand The herbicide triclopyr effectively controls this weed but is damaging to many native plant species To identify alternative herbicides 16 active ingredients representing eight chemical groups were applied to containergrown wandering Jew plants of various ages in three experiments In Experiment 1 triclopyr killed all plants (3 months old) while amitrole caused substantial damage to plants In Experiment 2 amitrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…(1) herbicide-treatment, (2) beetle-treatment, (3) no-treatment (T. fluminensis was left undisturbed), and (4) seedlings-only (T. fluminensis manually removed). The herbicide-treatment pots were treated following procedures described in Hurrell et al (2008). Thus, Grazon® (active ingredient 600 g/litre triclopyr) was applied at a rate of 0.72% ai plus 0.1% Pulse surfactant (800 g/litre active ingredient organomodified polydimethyl siloxane) with a knapsack sprayer to run-off.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) herbicide-treatment, (2) beetle-treatment, (3) no-treatment (T. fluminensis was left undisturbed), and (4) seedlings-only (T. fluminensis manually removed). The herbicide-treatment pots were treated following procedures described in Hurrell et al (2008). Thus, Grazon® (active ingredient 600 g/litre triclopyr) was applied at a rate of 0.72% ai plus 0.1% Pulse surfactant (800 g/litre active ingredient organomodified polydimethyl siloxane) with a knapsack sprayer to run-off.…”
Section: Methodsmentioning
confidence: 99%
“…Many germinating native seedlings are unable to tolerate the low light levels found underneath thick T. fluminensis stands commonly found in New Zealand (Standish et al 2001). Traditionally T. fluminensis has been controlled with herbicides (Department of Conservation 2012), but this is labour intensive and harms or kills many non-target species (Kelly & Skipworth 1984;Harrington & Schmitz 2007;Hurrell et al 2008). Further studies on different methods of control have found that light deprivation (shading out to 2-5% of full light) is an effective means of reducing T. fluminensis biomass (Standish 2002), but this is difficult to implement over large areas.…”
Section: Introductionmentioning
confidence: 99%
“…The search for alternative 'safer' herbicides has so far failed to produce any that equal triclopyr in efficacy. However, there are other herbicides that give some suppression of the weed, for example, amitrole and glyphosate (Hurrell et al 2008), and in the case of glyphosate, there is no soil residue. These herbicides may be better options for follow-up spot applications.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study comparing several herbicides for the control of wandering Jew (Hurrell et al 2008), triclopyr (Grazon 600 EC) was found to be the most effective, giving 98-100% control when it was applied to runoff at rates of 0.18 and 0.39% ai in three glasshouse experiments and at 0.72% ai in a field experiment. In other studies triclopyr has been shown to be similarly effective when applied to runoff at 0.42 and 0.84% ai (McCluggage 1998), at between 0.2 and 0.8% ai (Brown & Rees 1995) and at 0.4% ai (Standish 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Hurrell et al (2009) tested a range of herbicide rates on tradescantia and found that higher rates of herbicide were more effective at removing tradescantia biomass, but regrowth of tradescantia occurred regardless of the rate of herbicide used, and occurred sooner where a lower herbicide rate was used. In terms of effects of tradescantia control treatments on native plant communities, Standish (2002) found that native plant survival decreased in herbicide-treated plots compared to hand-weeded and untreated plots, whereas Hurrell et al (2008) found no evidence that herbicide rate influenced native seedling numbers or timing of emergence. There appear to be no published New Zealand field studies on the control of other ground cover weed species.…”
Section: Introductionmentioning
confidence: 99%